An Improvement of Facilities Layout Design in Retail Businesses: The Case Study of Surin Plaza Department Store - Rungtanakiat, Kesanee (2010)
Surin Plaza Department Store is the family business of Rungtanakiat family which has operated for almost 20 years in Surin, Thailand. Due to the growth of economic, technology, socialisation, and globalosation, the competition amongst retail businesses becomes more and more severe day by day which leads to the need to enhance the company performance. This paper then presents the need and the way Surin Plaza Department Store improves its performance. However, only the one focus of an issue related with operation management (the facility and layout design) is highlighted. As an untidy and frustration of Surin Plaza’s layout, the suggestions of rearrangement and departmentalisation of the products are illustrated by using some associated methods; the performance measurement (e.g. balance scorecard and benchmarking), the customer satisfaction survey (the using of questionnaire), and the layout methodology (Muther’s Systematic Layout Planning). Consequently, an outcome of the methodology application creates the two new recommended layouts for Surin Plaza. Additionally, the performance appraisal of the layouts will be discussed to show which type of layout is the best fit Surin Plaza and be appropriate to the real adaptation. Yet, in doing this, the lead time of customer flow travelling in each sample route which is set to be the key success factor of the layout improvement is compared between suggested alternatives to find out the best perform choice of layout design.